Africa’s youth and the future of food: IFPRI’s key takeaways from AFS forum 2025 - Omamo, Steven Were (Africa Food Systems Forum, 2025)
Over 60% of Africa’s people are under 25. By 2035, more young Africans will join the workforce each year than in the rest of the world combined, underscoring the urgency of the 2025 African Food Systems Forum (AFS Forum) theme: “Africa’s Youth: Leading Collaboration, Innovation, and Implementation of Agri-Food Systems Transformation.”